What is the role of genetic testing in the investigation of patients with suspected platelet function disorders?. (30th January 2014) - Daly, Martina E.; Leo, Vincenzo C.; Lowe, Gillian C.; Watson, Steve P.; Morgan, Neil V.
Summary Inherited platelet function disorders (PFDs), associated with normal or reduced platelet counts, account for a significant proportion of bleeding diatheses. Identification of the underlying genetic defects is difficult in the majority of cases due to the variable clinical expression of the bleeding symptoms and the redundancy of platelet receptor and signalling pathways, which add to the complexity of diagnosis. The gold standard method for phenotyping platelets, light transmission aggregometry (LTA), has allowed classification of functional defects in the majority of patients referred for investigation of suspected PFDs, while DNA‐based analysis has primarily played a confirmatory role and been restricted mainly to analysis of candidate genes. Recent advances in next generation sequencing have facilitated the identification of gene defects in patients with PFDs where the underlying genetic defect was previously unknown, especially when combined with genome‐wide linkage analysis. These studies have provided new insights into the mechanisms controlling platelet formation and function, and it is likely that, as understanding of the relationships between platelet phenotype and genotype increases and pipelines for the interpretation of genetic variations identified in patients are developed, DNA‐based analysis will play an increasingly important role in the first‐line investigation of patients with PFDs.